Plagioclase Hosted Melt Inclusion in Hypabyssal Rocks in Torud-Ahmad Abad Magmatic Belt - Yousefi, Fazilat; Papadopoulou, Lambrini; Sadeghian, Mahmoud; Wanhainen, Christina; Bark, Glenn (Bulletin of the Geological Society of Greece, 2019)
This study investigates for the first time melt inclusions (MI) that are found within fundamental minerals of subvolcanic rocks in Torud-Ahmad Abad magmatic belt. The Torud-Ahmad Abad magmatic belt is situated in south-southeast of Shahrood and belongs to the northern part of central Iran structural zone. Melt inclusions represent liquids that were trapped along growth zones (primary) or healed fractures of mineral phases, which crystallized from the silicate liquid as it cooled. Based on SEM analysis of these melt inclusions, their compositions are dacite, andesite and basaltic andesite. Thus, with the use of melt inclusions in the volcanic rocks of Torud-Ahmad Abad magmatic belt, we attempt to show the compositional evolution and origin of magma. The effective factors on magma evolution are magma mixing, fractional crystallization and crustal contamination.